2020
DOI: 10.1111/vop.12740
|View full text |Cite
|
Sign up to set email alerts
|

Corneoconjunctival transposition for the treatment of deep stromal to full‐thickness corneal defects in dogs: A multicentric retrospective study of 100 cases (2012‐2018)

Abstract: ObjectiveTo describe and evaluate the use of corneoconjunctival transposition (CTT) as a surgical treatment for canine deep stromal ulcers, descemetoceles, and full‐thickness corneal defects and to determine its efficacy in preserving corneal graft transparency and vision.Animals studiedOne hundred client‐owned dogs with deep stromal ulcers, descemetoceles, or full‐thickness corneal defects.MethodsMedical records of canine patients that underwent CCT, from 2012 to 2018, were reviewed. Only, patients with preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 35 publications
9
45
2
4
Order By: Relevance
“…Multiple corneal reconstructive techniques have been described utilizing conjunctiva, amniotic membrane, corneal tissue, and synthetic or bioengineered materials 3‐21 . The use of lamellar corneal grafting techniques can better preserve corneal transparency when compared to conjunctival pedicle grafting 18,22‐26 . Autologous grafts offer the advantage that they avoid immune‐mediated graft rejection and the need for corneal banking 6,18,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple corneal reconstructive techniques have been described utilizing conjunctiva, amniotic membrane, corneal tissue, and synthetic or bioengineered materials 3‐21 . The use of lamellar corneal grafting techniques can better preserve corneal transparency when compared to conjunctival pedicle grafting 18,22‐26 . Autologous grafts offer the advantage that they avoid immune‐mediated graft rejection and the need for corneal banking 6,18,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Gogova et al 27 found that euryblepharon and pigmentary keratitis were directly associated with decreased corneal clarity in post-operative CCT cases. In the present study, chronic post-operative complications resulting in corneal opacification included corneal pigmentation in 6/14 eyes (42.8%) and epithelial inclusion cysts in 5/14 eyes (35.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The corneoconjunctival transposition (CCT) is a modification of the corneoscleral transposition that uses conjunctiva rather than sclera. 1,[25][26][27][28][29] This surgical technique involves a sliding transposition of adjacent healthy cornea and attached bulbar conjunctiva, which allows for a clearer visual axis compared to other surgical techniques. However, a peripheral opacity may remain from the transposed limbus and conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations